Propuesta de un modelo de integración binacional en la gestión integrar de residuos sólidos en conjuntos residenciales para la república de Ecuador - Carabali Hernández, Asly Marcelli (Universidad Antonio Nariño, 2024)
This research project is aimed at knowing the type of management, storage and purpose of solid waste generated in residential complexes in the city of Cali with the scope that the Republic of Ecuador articulates the processes in the storage of solid waste according to the applicative application the Colombian environmental regulations, which provides the management parameters for an adequate implementation Within the methodology to obtain an approximation to results, the design of an instrument (survey) designed by the Faculty of Engineering of the Ecotec Technology University is proposed of Guayaquil Ecuador and the program of Engineering and International Trade of the Antonio Nariño University of the Neiva and Cali campuses with the above , a binational integration model is proposed between the Republic of Colombia and the Republic of Ecuador based on the exc